2006
DOI: 10.1007/s00122-006-0399-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the cultivated potato Solanum tuberosum L. Phureja Group using RAPDs and nuclear SSRs

Abstract: The Solanum tuberosum L. Phureja Group consists of potato landraces widely grown in the Andes from western Venezuela to central Bolivia, and forms an important breeding stock due to their excellent culinary properties and other traits for developing modern varieties. They have been distinguished by short-day adaptation, diploid ploidy (2n = 2x = 24), and lack of tuber dormancy. This nuclear simple sequence repeat (nSSR or microsatellite) study complements a prior random ampliWed polymorphic DNA (RAPD) study to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 47 publications
6
77
0
10
Order By: Relevance
“…Previous studies of genetic diversity using PCR based molecular markers reported similar results. Rocha et al (2010) and Ghislain et al (2006), observed low correlation between RAPD and SSR. Similarly, Milbourne et al (1997), obtained low correlation between RAPD, AFLP and SSR.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies of genetic diversity using PCR based molecular markers reported similar results. Rocha et al (2010) and Ghislain et al (2006), observed low correlation between RAPD and SSR. Similarly, Milbourne et al (1997), obtained low correlation between RAPD, AFLP and SSR.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Milbourne et al (1997), obtained low correlation between RAPD, AFLP and SSR. The reason for these findings could be due to the kind of information obtained by different molecular markers since different molecular markers amplify different repetitive and non-repetitive regions of the genome (Ghislain et al, 2006). Further analysis between RAPD and RAPD + ISSR showed low correlation (0.47) and ISSR and RAPD + ISSR showed a high correlation (0.74).…”
Section: Discussionmentioning
confidence: 99%
“…Ghislain et al (2006) from CIP showed the superior polymorphism detection power of nSSR as compared to RAPD markers. SSR and SNP techniques are presently considered the best methods to use in constructing a core collection and fingerprinting cultivars.…”
Section: The Potential Of Ssr Technique For Construction Of Core Collmentioning
confidence: 99%
“…phureja cv. Criolla is a diploid potato species that produces tubers with yellow skin and fl esh widely grown in the Andes from western Venezuela to the center of Bolivia (Ghislain et al, 2006). Th is crop has received increasing attention in Colombia as a potential exotic export product due to its excellent organoleptic properties; high levels of vitamins A, B, C; short production cycle and reduced tuber dormancy (Rodríguez et al, 2009).…”
Section: Phylogenetic Analysismentioning
confidence: 99%